Electrical Properties of the Base‐Substrate Junction in Freestanding Core‐Shell Nanowires (Adv. Mater. Interfaces 30/2022). Issue 30 (26th October 2022) - Koch, Juliane; Liborius, Lisa; Kleinschmidt, Peter; Weimann, Nils; Prost, Werner; Hannappel, Thomas
Abstract : Freestanding Nanowires In article number 2200948, Juliane Koch and co‐workers have electrically characterized the bottom‐up grown freestanding nanowires using a four‐point nanoprobe method. Due to its very high spatial resolution, conduction channels are identified at the nanowire base. This finding will have a high impact on the optimization of the electrical performance of freestanding nanowires for solar cells and for solar water splitting.